Megalith Cultures of the Kelabit Highlands through Space and Time Exhibition - Rafee, Y.M; Jussem, S.W; Awangko Hamdan, Awang Arshad; Siri, H. (2017)
Megalith Cultures of the Kelabit Highlands through Space and Time Exhibition, Teripun Community Museum, Bario, Sarawak